2019
DOI: 10.1371/journal.pone.0212910
|View full text |Cite
|
Sign up to set email alerts
|

The natural drug DIAVIT is protective in a type II mouse model of diabetic nephropathy

Abstract: There is evidence to suggest that abnormal angiogenesis, inflammation, and fibrosis drive diabetic nephropathy (DN). However, there is no specific treatment to counteract these processes. We aimed to determine whether DIAVIT, a natural Vaccinium myrtillus (blueberry) and Hippophae Rhamnoides (sea buckthorn) extract, is protective in a model of type II DN. Diabetic db/db mice were administered DIAVIT in their drinking water for 14 weeks. We assessed the functional, structural, and ultra-structural phenotype of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 37 publications
(58 reference statements)
0
7
0
Order By: Relevance
“…DIAVIT has been shown to protect against type II diabetic nephropathy in db/db mice, as indicated by amelioration of hyperglycaemia and albuminuria and increased glomerular water permeability. In addition, DIAVIT effectively prevents the altered splicing of VEGF-A and increases the ratio of VEGF-A 165 b/total VEGF-A 165 in podocytes in vitro …”
Section: Antidiabetesmentioning
confidence: 77%
“…DIAVIT has been shown to protect against type II diabetic nephropathy in db/db mice, as indicated by amelioration of hyperglycaemia and albuminuria and increased glomerular water permeability. In addition, DIAVIT effectively prevents the altered splicing of VEGF-A and increases the ratio of VEGF-A 165 b/total VEGF-A 165 in podocytes in vitro …”
Section: Antidiabetesmentioning
confidence: 77%
“…Additionally, we have recently reported 23 that a natural blueberry extract (DIAVIT) upregulates production of VEGF-A 165 b isoforms in podocytes. Indeed, when stably transfected HEK293 cells were treated with DIAVIT, the reporter dsRED/EGFP splicing ratio decreases as expected, in a dose-dependent manner (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In a case-controlled study, it was shown that serum VEGF-A was more preferable than that in plasma as a marker reflecting diabetic control in patients with type II diabetes, since a large portion of VEGF-A is derived from platelets ( 35 ). Kidney injury was partially prevented using DIAVIT, a natural Vaccinium myrtillus (blueberry) and Hippophae Rhamnoides (sea buckthorn) extract, due to the alteration of VEGF-A splicing in type II DN, particularly with delphinidin ( 43 ).…”
Section: Abnormal Angiogenesis In Dnmentioning
confidence: 99%